2011
DOI: 10.6009/jjrt.67.1533
|View full text |Cite
|
Sign up to set email alerts
|

The Precision of Half-value Layer Measurement on Mammography

Abstract: The half-value layer (HVL) is an important index of the image quality or radiation risk in mammography. Radiation risk of the breast tissue is evaluated with the average glandular dose. The HVL index is indispensable for the average glandular dose computations. We investigated the influence of multiple factors that affect HVL value, such as thickness or purity of the aluminum attenuator, detector material of dosimeter, fluctuation of X-ray output, detector location in X-ray field and so on, for accurate averag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…(5) In contrast, Ishii et al reported that for quality control, HVL should be measured using the same part of the same plate in the same filter set. (6) The European Reference Protocol for the Quality Control of the Physical and Technical Aspects of Digital Breast Tomosynthesis Systems (EUREF) guidelines (version 1.01, 2016) state that HVL should be measured with the X-ray tube fixed. (7) However, in actual DBT imaging, the X-ray tube is moved in a circular arc during imaging; therefore, measuring HVL with a mammography system equipped with a DBT requires the use of the device's onboard control mode, making it difficult to easily perform daily measurement in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…(5) In contrast, Ishii et al reported that for quality control, HVL should be measured using the same part of the same plate in the same filter set. (6) The European Reference Protocol for the Quality Control of the Physical and Technical Aspects of Digital Breast Tomosynthesis Systems (EUREF) guidelines (version 1.01, 2016) state that HVL should be measured with the X-ray tube fixed. (7) However, in actual DBT imaging, the X-ray tube is moved in a circular arc during imaging; therefore, measuring HVL with a mammography system equipped with a DBT requires the use of the device's onboard control mode, making it difficult to easily perform daily measurement in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the case of semiconductor dosimeters, the response varies depending on the energy of the x-rays [19]. For mammography, there are many reports that have indicated that the response changes significantly owing to differences in x-ray energy, and that the target-filter combination is limited [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…One of those factors affects the radiation quantity is HVL and plays an important role for the glandular dose investigations. On the other hand, it should be assures that radiation magnitude and radiation quality are within appropriate limits during the mammographic imaging process (6). The HVL of an X-ray beam can be calculated from measurements of air kerma with and without aluminium filters in the beam, or measured directly using a solid-state dosimetry system (7).…”
Section: Introductionmentioning
confidence: 99%